If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -14 = 4x + -8 Reorder the terms: -14 + x = 4x + -8 Reorder the terms: -14 + x = -8 + 4x Solving -14 + x = -8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -14 + x + -4x = -8 + 4x + -4x Combine like terms: x + -4x = -3x -14 + -3x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 -14 + -3x = -8 + 0 -14 + -3x = -8 Add '14' to each side of the equation. -14 + 14 + -3x = -8 + 14 Combine like terms: -14 + 14 = 0 0 + -3x = -8 + 14 -3x = -8 + 14 Combine like terms: -8 + 14 = 6 -3x = 6 Divide each side by '-3'. x = -2 Simplifying x = -2
| -6+6n=4n-6+4n | | 12+n+4+4=6n+5n | | 1-5n+2n=-3n+5n+1 | | -3x=7.5 | | 2.5(3-2x)+1=29 | | 5(y+5)=7y+25 | | -4m-2m+2=12m-2m+3 | | -11+x=1-2x | | 183=2.5x+8 | | 8(x-7y)= | | -2n-1-1=-2+2n | | (3-10y)=12 | | -5x+3(x+8)=16 | | -x^2+10+3= | | 2+4v-4=4+6v | | -35+7v=5(2v-7) | | 35=3+4x | | 8=8(b-5) | | 5x-2=-2+4x | | 61.25=0.15t+35 | | 1x+7=2x-3 | | 2-5x=-4x-2x | | 6(1+x)=24 | | 2n+n=9+6n+2-5 | | 3k-5=28 | | 2(6-q)=0 | | 6-2x-x=4x+6 | | .6m=6 | | 3(12-r)=30 | | 3(2x-6)+6(x-4)=-3(5-5x)+5x-17 | | 3x+7y+3=90 | | x^2+2x-81=0 |